Neurological diseases in relation to the blood–brain barrier - Rosenberg, Gary A (Nature Publishing Group, 2012)
Disruption of the blood–brain barrier (BBB) has an important part in cellular damage in neurological diseases, including acute and chronic cerebral ischemia, brain trauma, multiple sclerosis, brain tumors, and brain infections. The neurovascular unit (NVU) forms the interface between the blood and brain tissues. During an injury, the cascade of molecular events ends in the final common pathway for BBB disruption by free radicals and proteases, which attack membranes and degrade the tight junction proteins in endothelial cells. Free radicals of oxygen and nitrogen and the proteases, matrix metalloproteinases and cyclooxgyenases, are important in the early and delayed BBB disruption as the neuroinflammatory response progresses. Opening of the BBB occurs in neurodegenerative diseases and contributes to the cognitive changes. In addition to the importance of the NVU in acute injury, angiogenesis contributes to the recovery process. The challenges to treatment of the brain diseases involve not only facilitating drug entry into the brain, but also understanding the timing of the molecular cascades to block the early NVU injury without interfering with recovery. This review will describe the molecular and cellular events associated with NVU disruption and potential strategies directed toward restoring its integrity.